2016
DOI: 10.1186/s12885-016-2056-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of high FoxC2 expression in resectable non-small cell lung cancer, alone or in combination with E-cadherin expression

Abstract: BackgroundFoxC2 is an epithelial–mesenchymal transition (EMT) regulator which induces metastasis. The purpose of this study is to assess the prognostic value of FoxC2 expression in non-small cell lung cancer (NSCLC), alone or in combination with E-cadherin expression.MethodsA retrospective study was conducted using immunohistochemistry to investigate FoxC2 and E-cadherin expression in a cohort of 309 patients with surgically resected NSCLCs. The prognostic value of FoxC2 and E-cadherin on overall survival (OS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…This discrepancy might be due to the complex role of E-cadherin in metastasis or the different responses of cells which are treated with stimuli. However, most studies indicate that the reduction of E-cadherin expression in lung cancer cells is associated with low tumor differentiation, high metastasis, and poor outcome [46, 47]. Our data affirm these results and indicate a new TGF-β-miR-193a-E-cadherin pathway to promote TGF-β-induced EMT in lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…This discrepancy might be due to the complex role of E-cadherin in metastasis or the different responses of cells which are treated with stimuli. However, most studies indicate that the reduction of E-cadherin expression in lung cancer cells is associated with low tumor differentiation, high metastasis, and poor outcome [46, 47]. Our data affirm these results and indicate a new TGF-β-miR-193a-E-cadherin pathway to promote TGF-β-induced EMT in lung cancer.…”
Section: Discussionsupporting
confidence: 87%
“…However, in addition to lymphatics, these protein are expressed in various cell types and contribute to multiple molecular processes, including those in malignancies, as it has been demonstrated in a number of recent comprehensive reviews (54)(55)(56)(57)(58)(59)(60)(61)(62). This may provide an explanation for inconsistent data on the expression of analyzed proteins in cancer and their impact on tumor progression and clinical outcome (63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies on E-Cadherin expression in NSCLC tested by immunohistochemistry report conserved protein expression ranging from 32% to 88% in tumors depending on the IHC cutoff value. [22][23][24][25][26][27][28][29] Moreover, an association of E-Cadherin loss of IHC expression and the N+ status of patients was reported in several stages I to IV NSCLC cohorts. 23,24,[28][29][30][31][32][33] Two other studies that analyzed CDH1 expression in stage I to III NSCLC tumors reported an opposite association between CDH1 expression and N status, with one study reporting preserved CDH1 expression and the other study reporting lost CDH1 expression.…”
Section: Discussionmentioning
confidence: 99%